Diagnostic utility of Ki-67 and Cyclin D1 immunostaining in differentiation of psoriasis vs. other psoriasiform dermatitis - Engin Sezer; Almut Böer-Auer; Emel Cetin; Fatma Tokat; Emel Durmaz; Sedef Sahin; Umit Ince (Mattioli1885, 2015)
Background: Differentiation of psoriasis from non-psoriasis psoriasiform dermatitis (NPPD) may be difficult for dermatopathologists, as lack of distinctive histopathological features in a subset of cases may cause confusion in diagnosis. Objective: As the prototype of psoriasiform dermatitis, psoriasis is a hyperproliferative skin disorder with increased epidermal turnover compared with NPPD, we investigated the role of proliferation markers, Ki-67 and Cyclin D1 as diagnostic tools to differentiate psoriasis from other psoriasiform dermatitis. Methods: Histopathological specimens of psoriasis (n = 35) and NPPD (n = 36, 14 pityriasis rubra pilaris, 12 pityriasis rosea and 10 lichen simplex) cases were reviewed and immunohistochemically stained for Ki-67 and Cyclin D1. Ki-67 and Cyclin D1 positive cells were counted for suprabasal, and total epidermal immunostaining per mm2. Results: Suprabasal and total epidermal cell counts for Ki-67 were found to be significantly higher in the psoriasis group compared with the NPPD group (p < 0.05). An important and interesting feature was the presence of a cut-off value for the suprabasal/total epidermal cell count ratio of 75% for Ki-67 immunostaining, which was higher in all patients having psoriasis (range, 77.1% - 92.4%) and lower in all NPPD cases (range, 21.0% - 73.3%). However, suprabasal Cyclin D1 cell counts were higher in the psoriasis group compared with the NPPD group (p < 0.05), total epidermal Cyclin D1 cell counts were not statistically significant in either group (p = 0.167), and a cut-off value for suprabasal/total epidermal cell count ratio to distinguish these two entities was not detected using this immunostain. Conclusions: We suggest that Ki-67 is a more sensitive marker than Cyclin D1 in terms of having a cut-off value of 75% for the suprabasal/total epidermal immunoreactive cell count ratio, which we believe could be useful for dermatopathologists in differentiating psoriasis from other psoriasiform dermatitis.